Search for Conjugal Bliss in Cat on a Hot Tin Roof - Ahmad Tabasum, Irshad; Kamal Khan, Muhammad (The Journal of Humanities & Social Sciences, 2023)
The conjugal life of Maggie and Brick is on the verge of collapse because the former is heterosexual and the latter is homosexual but Maggie leaves no stone unturned to save such a life. She has to fight on two fronts. Firstly, she has to restore the broken masculinity of Brick into wholeness. She revitalizes Brick’s passive and latent physicality with her aggressive sexuality. She tries to arouse his sexual jealousy by mentioning how other men show sensual desire for her. Secondly, her childlessness marginalizes her in the worst way. She passes through endless envy when she compares her childlessness with the five children of her sister-in-law and becomes catty whenever she faces them. It is true that she tells a lie about her pregnancy because she knows that truth will not work in the world she lives. Moreover, her love for her husband is so potent that she succeeds in convincing him to turn the lie into a reality. Maggie is blunt in her love and hatred. She is a strange mixture of kindness and cruelty. In this way she not only outwits all those ready to destroy her marital bliss but also rejuvenates the paralyzed sexuality of her husband with her aggressive sexuality. So love is a force with which Maggie faces her predicament and emerges stronger, happier and better off than before.